Adsorption behavior and mechanism of 2, 4, 6‐trinitrotoluene by functionalized polystyrene nanospheres. Issue 6 (10th October 2012) - Zhang, Yihe; Wang, Xinyan; Lv, Fengzhu; Chu, Paul K.; Ye, Zhengfang; Zhou, Fengshan; Zhang, Rui; Wei, Fangfang
Abstract 3‐Methactyloxylpropyltrimethoxyl silane (KH‐570)‐modified polystyrene (PS) nanospheres and PS nanospheres were prepared and used to absorb 2, 4, 6‐trinitrotoluene. The absorbed amount reached 2.81 mg/g for KH‐570‐modified PS nanospheres at 298 K and pH 6 when the initial 2, 4, 6‐trinitrotoluen concentration was 50 mg/L. The kinetic results showed that the pseudo‐second‐order model fit the two kinds of absorbents. The adsorption mechanism study revealed that the driving forces of adsorption were combined actions of Π–Π stacking interaction, hydrogen interaction, and hydrophobic interaction. The prepared nanospheres were reusable. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013